Endoscopic Ultrasonography of the Pancreas: New Advances - Hayakawa, Tetsuo; Jin, Chun X; Hirooka, Yoshiki (JOP. Journal of the Pancreas, 2016)
No abstract available. Image: Surgical oparation at Aichi Prefectural Public Hospital (approx. 1880). From Nagoya University School/Graduate School of Medicine.